KEPENTINGAN THAILAND DALAM PENERAPAN KEBIJAKAN LEGALISASI GANJA - Kama, I Putu Satya; Intan Prameswari, Anak Agung Ayu; Sushanti, Sukma (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
Thailand was one of the biggest cannabis producing countries in the world in the 80s. After signing the UN regulations on drugs (Narcotics, Psychotropics and Addictive Substances), Thailand made new regulations and strongly opposed the distribution of cannabis in the country. By implementing a "war on drugs" policy and a "zero tolerance" attitude, Thailand has had a history of the biggest human rights violations in ASEAN related to cannabis. After Thailand became the first country to ban cannabis use, now Thailand has become the first country to legalize marijuana for medical purposes in ASEAN. This study aims to analyze the reasons why the Government of Thailand implemented a policy of legalizing medical marijuana in 2019. Using the National Interest framework through qualitative descriptive analysis, it was found that Thailand issued a policy of legalizing marijuana to meet the economic interests and security interests of the country. Keywords: Thailand, War on Drugs, Legalization of Medical Marijuana, National Interest, Economic Security.